LINGUOCULTURAL ANALYSIS OF REALIA IN THE WORK “SHUM BOLA” (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the realia found in the famous work Shum bola by Gʻafur Gʻulom from a linguocultural perspective. During the research, linguistic units expressing national and cultural features in the work are identified, and their functions and semantic characteristics in the literary text are examined. Through these realia, the ways in which the lifestyle, traditions, social environment, and cultural values of the Uzbek people are reflected are highlighted. The study also discusses the role of realia in creating national color in the text and analyzes their linguocultural significance. Semantic, contextual, and linguocultural analysis methods were used in the research process.
Keywords: realia, linguoculturology, national culture, literary text, Uzbek traditions, linguocultural analysis, mentality.